Crystal Structure of the ZrO Phase at Zirconium/Zirconium Oxide Interfaces1. Issue 2 (27th June 2014) - Nicholls, Rebecca J.; Ni, Na; Lozano‐Perez, Sergio; London, Andrew; McComb, David W.; Nellist, Peter D.; Grovenor, Chris R.M.; Pickard, Chris J.; Yates, Jonathan R.
<x xml:space="preserve">Abstract</x> Zirconium‐based alloys are used in water‐cooled nuclear reactors for both nuclear fuel cladding and structural components. Under this harsh environment, the main factor limiting the service life of zirconium cladding, and hence fuel burn‐up efficiency, is water corrosion. This oxidation process has recently been linked to the presence of a sub‐oxide phase with well‐defined composition but unknown structure at the metal–oxide interface. In this paper, the combination of first‐principles materials modeling and high‐resolution electron microscopy is used to identify the structure of this sub‐oxide phase, bringing us a step closer to developing strategies to mitigate aqueous oxidation in Zr alloys and prolong the operational lifetime of commercial fuel cladding alloys.